Exploring the structural, elastic, electronic and thermal properties of Ti-Al-Me (Me = Cu, Fe and Ni) alloys by first-principles studies - Yulai Song; Yiming Li; Zheng Zhang; Xiaolin Zhao; Jiaxin Tang; Junjie Ni (Scientific Reports)
Abstract The welding of titanium alloys is an important topic in today’s industrial field, and the interaction between the solder and the base material is crucial for the quality of the welded parts. The structural, elastic, electronic, and thermal properties of Ti-Al-Me (Me = Cu, Fe and Ni) alloys (TAMs) with the face-centered cubic structures were investigated using plane-wave pseudo potential method in the framework of density functional theory. Based on the calculated elastic constants combined with empirical and semi-empirical formulas, physical properties including ductility/brittleness, hardness and anisotropy were calculated. Moreover, thermodynamic information such as entropy, enthalpy, free energy, heat capacity and heat transfer coefficient were calculated. The results showed that TiAlFe2 had the highest thermal conductivity coefficient, and the heat capacities of all phases gradually approached the Dulong-Petit limit at high temperatures, while they conformed to the Debye’s temperature law at low temperatures. Furthermore, the electronic structure calculation results indicate that all compounds are metallic and the d orbital plays an important role in the hybridization process. These calculation results are of great practical importance for understanding the basic physical and chemical properties of TAMs, clarifying their applications in the welding of aerospace and aircraft structural components to make sensible material selection.